DEVELOPMENT OF STUDENT WORKSHEET WITH PROJECT-BASED LEARNING-ORIENTED TO IMPROVE SCIENCE PROCESS SKILLS IN GREEN CHEMISTRY USING ORANGE PEEL WASTE - Faatih Ridlo Kusuma; Mitarlis Mitarlis (Universitas Negeri Surabaya, 2026)
This study aimed to determine the feasibility of a Project Based Learning-oriented SAS to improve students’ science process skills on green chemistry material. The focus of this study was the development of a project-based SAS incorporating green chemistry principles to improve science process skills, including observing, classifying, predicting, measuring, concluding, and communicating. This study employed a Research and Development (R&D) method using the 4D development model (define, design, develop, and disseminate), but was limited to the develop stage. The subjects of this study were 36 tenth-grade students at a high school in Surabaya. The feasibility of the developed SAS was evaluated based on aspects of validity, practicality, and effectiveness. The validity results showed that the SAS obtained a mode score of 4–5 with good and very good criteria. The practicality results showed a learning implementation percentage of 87,5%, student activity observation results of 84,6%, and student response questionnaire results of 94%, all categorized as very good. The effectiveness results showed a classical completeness score of 97,2% and an improvement in students’ science process skills, with N-Gain scores ranging from medium-g to high-g categories. Therefore, the developed SAS is feasible to be used as a chemistry learning material.